Exposure to noise and its physiological effects on steel mill workers: a case study / Siti Nur Atiqah Azmi ... [et al.] - Azmi, Siti Nur Atiqah; Radzran, Ahmad Syahir; Mat Daud, Mohamad Aizuddin Amin; Rajan, Shantakumari (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Noise is a well-known occupational hazard worldwide and hypertension a recognized risk factor for cardiovascular disease. This study investigated the immediate effects of noise exposure on blood pressure in an occupational setting. Systolic and diastolic blood pressure was measured before and after an 8-hour work period and continuous 8-hour personal noise exposure for 19 steel industry workers. Sixty-three percent of the workers were exposed to noise ranging between 75-85 dB(A) while 37% of the workers were exposed to noise above 85 db(A) which is above the Permissible Exposure Limit (PEL) as stated in the First Schedule of the Factories and Machinery (Noise Exposure) Regulations Act 1989. There was a significant difference in both systolic and diastolic blood pressure after an eight-hour work period (p < 0.05). We were able to demonstrate that noise exposure is independently associated to hypertension. These results are consistent with other studies to verify the occurrence of non-auditory effects in workers exposed to noise. Therefore, it is important that noise exposure limits are established aiming at preventing both hearing and non-hearing health effects